2019
DOI: 10.1016/j.molbiopara.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Protean permeases: Diverse roles for membrane transport proteins in kinetoplastid protozoa

Abstract: Kinetoplastid parasites such as Trypanosoma brucei, Trypanosoma cruzi, and Leishmania species rely upon their insect and vertebrate hosts to provide a plethora of nutrients throughout their life cycles. Nutrients and ions critical for parasite survival are taken up across the parasite plasma membrane by transporters and channels, polytopic membrane proteins that provide substrate-specific pores across the hydrophobic barrier. However, transporters and channels serve a wide range of biological functions beyond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Currently, chemotherapy is the only available option against trypanosomes as efforts to develop a vaccine have been thwarted by the international community, however, the development of trypanocidal resistance has become a realistic threat especially for persons living in endemic regions (103,145,157,158). Trypanosoma transport proteins [on the surface of the parasite (see Table 4)] are responsible for pathogen survival; and trypanocidal resistance has been associated with changes in the pathogen transportome leading to dysfunction and a loss in therapeutical potential once drugs can no longer be absorbed by the parasite (152)(153)(154)159). This justifies the need to promote further research for the discovery of novel chemotherapeutical options for the control of trypanosomiasis.…”
Section: Trypanocidal Resistancementioning
confidence: 99%
“…Currently, chemotherapy is the only available option against trypanosomes as efforts to develop a vaccine have been thwarted by the international community, however, the development of trypanocidal resistance has become a realistic threat especially for persons living in endemic regions (103,145,157,158). Trypanosoma transport proteins [on the surface of the parasite (see Table 4)] are responsible for pathogen survival; and trypanocidal resistance has been associated with changes in the pathogen transportome leading to dysfunction and a loss in therapeutical potential once drugs can no longer be absorbed by the parasite (152)(153)(154)159). This justifies the need to promote further research for the discovery of novel chemotherapeutical options for the control of trypanosomiasis.…”
Section: Trypanocidal Resistancementioning
confidence: 99%
“…These DEGs plus the downregulated gene putatively coding for cytosolic malate dehydrogenase (TcCLB.506937.10) and the upregulation of several genes coding for amino acid permeases and transporters (5 putative permeases and one transporter (TcCLB.508923.10, TcCLB.511325.40, TcCLB.507811.100, TcCLB.511325.50, TcCLB.507101.10, TcCLB.511325.25) describe a global profile coinciding with the starvation-induced metabolic switch from glucose to amino acid consumption previously reported ( Barisón et al., 2017 ). A wide range of biological functions has been proposed for cell or intracellular membrane transport proteins of kinetoplastids, establishing physiological properties such as membrane potential and responses to osmolarity, and in sensing and responding to changes in the environment ( Landfear, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Here, different drug combination regimens were tested in vitro on the epimastigote culture, finding that a simultaneous combination of IVM-BZN and IVM-NFX showed mainly additive effects; however, some combinations showed significant antagonistic or synergic effects. These effects could be explained by different described mechanisms of IVM action, including an antagonism by increasing detoxification processes induced by this drug that avoid the effects of NFX or BZN ( Lespine et al., 2007 ; Ménez et al., 2012 ; Nodari et al., 2020 ) or a synergism by inhibiting the activity of P-gp, a member of the superfamily of transporters ABC (ATP-binding cassette), that enhances the cytotoxicity of other drugs ( Furusawa et al., 2000 ; Landfear, 2019 ). As mentioned by other authors, the in vitro assays about the interaction between two drugs are usually the first-step studies, although the observed results do not necessarily reflect the in vivo effects; pharmacokinetic and host factors (as the immune response) may lead to different outcomes due to the modification of the effective exposure of the parasites to the drugs ( Vincent et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%